Childhood infections and common carotid intima media thickness in adolescence. (8th November 2019) - Prins-van Ginkel, A. C.; Bruijning-Verhagen, P. C. J.; Wijga, A. H.; Bots, M. L.; Gehring, U.; van der Hoek, W.; Koppelman, G. H.; van Rossem, L.; Uiterwaal, C. S. P. M.; Smit, H. A.; van der Sande, M. A. B.
Abstract: Atherosclerotic changes can be measured as changes in common carotid intima media thickness (CIMT). It is hypothesised that repeated infection-associated inflammatory responses in childhood contribute to the atherosclerotic process. We set out to determine whether the frequency of infectious diseases in childhood is associated with CIMT in adolescence. The study is part of the Prevention and Incidence of Asthma and Mite Allergy (PIAMA) population-based birth cohort. At age 16 years, common CIMT was measured. We collected general practitioner (GP) diagnosed infections and prescribed antibiotics. Parent-reported infections were retrieved from annual questionnaires. Linear regression analysis assessed the association between number of infections during the first 4 years of life and common CIMT. Common CIMT measurement, GP and questionnaire data were available for 221 participants. No association was observed between the infection measures and CIMT. In a subgroup analysis, significant positive associations with CIMT were observed in participants with low parental education for 2–3 or ⩾7 GP diagnosed infections (+26.4 µm, 95% CI 0.4–52.4 and +26.8 µm, 95% CI 3.6–49.9, respectively) and ⩾3 antibiotic prescriptions (+35.5 µm, 95%CI 15.8–55.3). Overall, early childhood infections were not associated with common CIMT in adolescence. However, a higher number of childhood infections might contribute to the inflammatory process of atherosclerosis in subgroups with low education, this needs to be confirmed in future studies.